1998
DOI: 10.1152/ajpheart.1998.274.5.h1655
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic sensory denervation on Ca2+-induced relaxation of isolated mesenteric resistance arteries

Abstract: We recently reported that Ca2+-induced relaxation could be linked to a Ca2+ receptor (CaR) present in perivascular nerves. The present study assessed the effect of chronic sensory denervation on Ca2+-induced relaxation. Mesenteric resistance arteries were isolated from rats treated as neonates with capsaicin (50 mg/kg), vehicle, or saline. The effect of cumulative addition of Ca2+ was assessed in vessels precontracted with 5 μM norepinephrine. Immunocytochemical studies showed that capsaicin treatment signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
31
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 22 publications
6
31
2
Order By: Relevance
“…Increasing [Ca 2ϩ ] o from 1.5 to 5 mM caused a concentration-dependent relaxation of these arteries except for the coronaries, which showed very little response (43), suggesting that Ca o 2ϩ was activating a neuronally mediated vasodilatory response possibly through the CaR. Further studies with rat mesenteric arteries demonstrated that this most probably was the case (10,34,44) and that the neuronally released vasodilator substance was a cannibinoid (21). However, these studies were all performed using arteries preconstricted by agonists and under isometric conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing [Ca 2ϩ ] o from 1.5 to 5 mM caused a concentration-dependent relaxation of these arteries except for the coronaries, which showed very little response (43), suggesting that Ca o 2ϩ was activating a neuronally mediated vasodilatory response possibly through the CaR. Further studies with rat mesenteric arteries demonstrated that this most probably was the case (10,34,44) and that the neuronally released vasodilator substance was a cannibinoid (21). However, these studies were all performed using arteries preconstricted by agonists and under isometric conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, CaR expression has been reported in the perivascular sensory nerves of rat small mesenteric (10), basilar, renal, and coronary arteries (43). Increasing [Ca 2ϩ ] o (1.25-5 mM) induced a concentration-dependent relaxation of rat small mesenteric arteries precontracted with norepinephrine that was dependent on intact perivascular nerves (10,34,44) and associated with the release of a neurally derived relaxing factor, possibly the cannabinoid anandamide (21).…”
mentioning
confidence: 99%
“…calcium; dorsal root ganglion; posttranscriptional modification; glycosylation CHANGES IN THE CONCENTRATION of interstitial Ca 2ϩ as have been shown to occur in tissues involved in transcellular Ca 2ϩ movement (26,27) can modulate the function of a variety of cell types by activating a membrane-spanning, G protein-coupled receptor for extracellular Ca 2ϩ (7). The first molecular evidence for a Ca 2ϩ -sensing receptor (CaSR) was reported by Brown et.…”
mentioning
confidence: 99%
“…1 Among the findings that support this pathway are the demonstration that dorsal root ganglia and perivascular sensory nerves express a protein that is immunoreactive with antibodies raised against the parathyroid Ca 2ϩ receptor 2 and that the magnitude of Ca 2ϩ -induced relaxation positively correlates with Ca 2ϩ receptor-positive nerve density. 3 The relaxation is inhibited by nonselective antagonism of potassium (K ϩ ) channel activity with precontraction in depolarizing concentrations of KCl and pretreatment with tetraethyammonium 2 and by selective blockade of large conductance K Ca channels with iberiotoxin 4 and charybdotoxin. 5 Additional work has shown that the relaxation is blocked by the selective CB 1 receptor antagonist SR141716A and is mimicked by anandamide, 4 an endocannabinoid, which has been shown to be formed in neuronal tissue.…”
mentioning
confidence: 99%